Improving Language Acquisition in Sensory Deficit Individuals with Mobile Application. (2016) - Amrutha, C.U.; Davis, Nithya; Samrutha, K.S.; Shilpa, N.S.; Chunkath, Job
Abstract: This paper discusses the problems faced by hearing impaired individuals in India and the use of technology to make their interaction easier. World over sign language is used for interaction among hearing impaired people. Sign language is developed and standardized in many developed nations like United States of America, United Kingdom etc. This has resulted in American Sign Language (ASL), British Sign Language (BSL) respectively. Language acquisition is a major requirement during the initial development stage of a sensory deficit subject. The language skills help an individual's ability to express self, aids cognitive skills and thought process. In India the pedagogy based on Indian Sign Language (ISL) is developing. Language learning using a multimedia based application is found helpful for sign language users. This paper discusses the development of a mobile application for sensory deficit people for language acquisition. An Android based learning system for hearing impaired individuals, which translate text to Indian sign language videos and images are developed.